Adult-onset Krabbe disease presenting with progressive myoclonic epilepsy and asymmetric occipital lesions: A case report - Wang, Yu; Wang, Su-yue; Li, Kai; Zhu, Yu-long; Xia, Kun; Sun, Dan-dan; Ai, Wen-long; Fu, Xiao-ming; Ye, Qun-rong; Li, Jun; Chen, Huai-zhen (Frontiers in Neurology, 2022)
Krabbe disease (KD), also known as globoid cell leukodystrophy, is a rare autosomal recessive condition caused by mutations in the galactocerebrosidase (GALC) gene. KD is more common in infants and young children than in adults. We reported the case of an adult-onset KD presenting with progressive myoclonic epilepsy (PME) and cortical lesions mimicking mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome. The whole-exome sequencing (WES) identified a pathogenic homozygous missense mutation of the GALC gene. Parents of the patient were heterozygous for the mutation. The clinical, electrophysiological, and radiological data of the patient were retrospectively analyzed. The patient was a 24-year-old woman presenting with generalized seizures, progressive cognitive decline, psychiatric symptoms, gait ataxia, and action-induced myoclonus. The brain magnetic resonance imaging (MRI) revealed a right occipital cortical ribbon sign without any other damage. This single case expands the clinical phenotypes of adult-onset KD.